MENGUJI KHARISMA KYAI DALAM KEHIDUPAN MASYARAKAT MADURA JEMBER JAWA TIMUR - Al Khanif Al Khanif (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2011)
Charisma of kyai has been facing more socio-cultural challenge overtime due to the development of society. The intervention of governmentto eliminate poverty and enhance the quality of education, globalization,modernization as well as the change of paradigm within society hasinfluenced paternalistic tradition. However, the role of kyai in Maduresesociety has performed differently. In socio-cultural tradition, kyai hasstill played significant role to shape people’s understanding about worldview especially on religious and cultural values. Additionally, kyai hasalso still influenced people’s political view and even has more power toshape its society by challenging its organization structural hirearkhy.This paper comes with conclusion that kyai for Madurese people is stillcharismatic because they have extra ordinary knowledge to responsesocial problem. Additionally, people perceive kyai as a representative ofcreative minority group.